PENGARUH KOMITMEN ORGANISASI, KECERDASANEMOSIONAL, DAN STRES KERJA KARYAWAN TERHADAP PERILAKU KEWARGAAN ORGANISASI (PKO) PADA PT XYZ - Shela Callista Putri (2022)
This research is a quantitative study that aims to determine the effect of organizational commitment, emotional intelligence, and work stress on organizational citizenship behavior. This study used 137 PT XYZ employees, using a purposive sampling technique. The analysis technique used is path analysis and the data is processed using SmartPLS 3.0. The results of the test obtained: (1) organizational commitment has a positive and significant effect on organizational citizenship behavior of PT XYZ (2) emotional intelligence has a positive and significant effect on organizational citizenship behavior of PT XYZ (3) work stress has a negative and significant effect on citizenship behavior PT XYZ organization.